Tinjauan Yuridis Perlindungan Hukum terhadap Pekerja Migran Indonesia Berdasarkan Undang-Undang Nomor 18 Tahun 2017 (International Forum of Researchers and Lecturers, 2024)
The phenomenon of Indonesian labor migration abroad is an important strategy for improving community welfare and contributing to national economic growth. Every year, thousands of Indonesian migrant workers (TKI) leave for various countries in hopes of finding better job opportunities. However, the reality they face often falls short of expectations, as many migrant workers experience discrimination, exploitation, and violence. Law Number 18 of 2017 on the Protection of Indonesian Migrant Workers (UU PPMI) serves as a legal framework to provide comprehensive protection, yet its implementation still faces significant challenges. This research employs a normative legal method to analyze the effectiveness of UU PPMI in providing legal protection for migrant workers. The analysis reveals that structural, technical, and legal obstacles hinder the effectiveness of protection. Therefore, a comprehensive approach is needed, including strengthening institutions, enhancing human resource capacity, and fostering collaboration among government, private sector, and civil society. This study aims to contribute to improving the conditions of Indonesian migrant workers and promoting more effective protection.